2022
DOI: 10.34096/arqueologia.t28.n2.9915
|View full text |Cite
|
Sign up to set email alerts
|

Análisis zooarqueológico del sitio Álvarez 4 (noroeste de Patagonia, Argentina). Un aporte al estudio de la subsistencia de los grupos humanos de la cuenca media del río Limay durante el Holoceno tardío

Abstract: Se presenta el análisis zooarqueológico y tafonómico del sitio Álvarez 4, un alero emplazado en la cuenca media del río Limay en el noroeste de Patagonia, Río Negro, Argentina. Los restos faunísticos provienen del Período I (1100 ± 70 AP), del Período II (210 ± 90 AP), de la cuadrícula C3 (perturbada antrópicamente) y de la Capa Superficial (210 ± 90 AP). Se determinó una incidencia baja de procesos postdepositacionales. Se registró la acción de otros procesos tafonómicos como perturbación sedimentaria por cau… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 4 publications
1
2
0
Order By: Relevance
“…Although this taphonomic signature was recorded throughout the entire LL sequence, it increased toward the last ca. 1000 years BP (periods E and F), in line with the exploitation of more faunal resources at this site (Guillermo et al, 2022), and at regional level (e.g. Cordero, 2011;Fernández et al, 2016Fernández et al, , 2017bGuillermo et al, 2020aGuillermo et al, , 2020bGuillermo et al, , 2021.…”
Section: Different Taphonomic Trajectories and Their Small Mammal Tax...supporting
confidence: 65%
See 2 more Smart Citations
“…Although this taphonomic signature was recorded throughout the entire LL sequence, it increased toward the last ca. 1000 years BP (periods E and F), in line with the exploitation of more faunal resources at this site (Guillermo et al, 2022), and at regional level (e.g. Cordero, 2011;Fernández et al, 2016Fernández et al, , 2017bGuillermo et al, 2020aGuillermo et al, , 2020bGuillermo et al, , 2021.…”
Section: Different Taphonomic Trajectories and Their Small Mammal Tax...supporting
confidence: 65%
“…The zooarchaeological and taphonomic studies of the mollusks, fishes, birds, and medium and large mammals (more than 15,000 specimens) have revealed that the subsistence of the human groups that inhabited LL was based on the exploitation of Lama guanicoe and was complemented with Rhea pennata and small size mammals such as Conepatus chinga, Chaetophractus villosus, Lycalopex gymnocercus, Lycalopex culpaeus, and Leopardus sp. (Guillermo et al, 2022). One exotic species was also identified O. o. aries, although its incorporation into human subsistence for historical context was secondary (Guillermo et al, 2022).…”
Section: Chronostratigraphic Context Of Epullán Grande Cavementioning
confidence: 99%
See 1 more Smart Citation